Cloud Computing and Networking for SmartFarm AgriTech. (7th June 2022) - Rathod, Meenakshi L.; Shivaputra, A.; Umadevi, H.; Nagamani, K.; Periyasamy, Selvakumar
Abstract : In this paper, the implementation of SmartFarm AgriTech is done using IoT and cloud computing. The current world population is 7.9 billion and supposed to reach 12 billion by 2050, and it is difficult to feed such population in the future. So, for feeding the entire population, the agriculture sector should be embedded with the latest technologies. People living in urban city will be covered with their work and day to day activities which makes it really difficult to travel the village and monitor their cultivation regularly. Without proper maintenance of farms, it is hard to get the desired results, so using the cloud computing, IOT, networking, and many other technologies, one can easily maintain and monitor the crops, weather, water, and spraying fertilizers whenever needed. This SmartFarm AgriTech System is designed using Raspberry Pi and Arduino as the main microcontrollers to control the various sensors, relay-switch, and motor. AWS and ThingSpeak are used to create server and APIs to collect and store the data through Internet or via a Local Area Network (LAN). In addition to that, a GUI (Graphical User Interface) application is also created to control and monitor the data coming from Raspberry Pi and Arduino board.